Pulmonary embolism and renal artery thrombosis in a patient with patent foramen ovale - Bova, Carlo; Calcaterra, Rossana; de Vuono, Andrea; Pignataro, Francesca Serena; Fiaschi, Elio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Paradoxical embolism is a rare condition in which a thrombus migrates from the venous system to the arterial circulation, usually through a patent foramen ovale (PFO). Pulmonary embolism (PE) and isolated occlusion of one renal artery has been seldom reported. Methods. We describe a case of a 47-year old white man with a one-month history of exertional dyspnea who was admitted to our hospital for  severe pain in the right lumbar region. Results. A computed tomography showed  PE and a thrombotic occlusion of the right renal artery. A trans-thoracic echocardiogram documented a PFO with right to left shunt. Magnetic resonance imaging of the brain and venous compression ultrasonography of the lower extremities were normal. Therapeutic anticoagulation was started. Conclusions. Pulmonary embolism and thrombotic occlusion of one renal artery is a rare manifestation of paradoxical embolism. Exertional dyspnea is an atypical manifestation of PE and can delay the diagnosis